Highly Efficient Conservative Treatment of Pectus Carinatum in Compliant Patients - Loff, Steffan; Sauter, Hartwig; Wirth, Thomas; Otte, Ralf (European Journal of Pediatric Surgery, 2015)
Purpose Pectus carinatum is a thoracic deformity, which causes severe psychological problems for affected patients but almost no physical limitations. Invasive procedures are difficult to justify for this reason. We present a conservative therapy which leads to complete resolution in most cases when performed properly.Methods Between January 2008 and December 2012, 69 patients from 4 to 17 years with pectus carinatum were treated with a custom-fitted brace. Patients were stratified in children, adolescents, and adults.Results Mean therapy time was 7 months. Mean time of daily brace wearing was 12 to 15 hours. The results were evaluated by pictures taken before and after the therapy and from a patient interview. Standardized lateral views revealed a mean correction angle of 10 degrees in the children's group and 5 degrees in the adolescent group. In the adolescent group, 82% of patients judged the result as “excellent” or “good.” In this large group with 56 patients, those who reported the result “unchanged” had a mean daily brace wearing time of 8.73 hours, those who judged the result as “good” 14.53 hours, and those who judged the result as “excellent” 18.36 hours.Conclusion Our results show that pectus carinatum is efficiently treated with a customized brace therapy within 7 to 12 months. Best correction can be achieved in children and young adolescents. Daily brace-wearing time should be above 14 hours, ideally 24 hours. Duration of the treatment should be around 1 year. Treatment results correlate directly with the cooperation of the patients.
Keywords: pectus carinatum; conservative therapy; thoracic deformity